Echoes of Empire, Sounds of Nation: Keroncong and the Politics of Musical Canon in Postcolonial Indonesia - Nuristama , Ramadhina Ulfa (Harmonia : Journal of Music and Arts, 2025)
Keroncong music, a hybrid genre rooted in Portuguese colonial influence and indigenous traditions, has undergone significant transformation over centuries, culminating in its institutionalization as a national symbol in Indonesia. This article investigates the evolution of Keroncong across five distinct phases beginning with the Tugu community’s early preservation efforts, through colonial and postcolonial media dissemination, to contemporary reinterpretations by diaspora and youth movements. The study applies a multidisciplinary methodology combining historical periodization, media archaeology, musicological analysis, and cultural theory. Through archival research and comparative analysis, the article identifies the critical roles of NIROM and RRI in canon formation, emphasizing how broadcasting and state cultural policy promoted Langgam Jawa and iconic compositions like “Bengawan Solo” as representative of national identity. It further explores how canonization processes, while preserving cultural memory, can also marginalize regional and minority expressions. Comparative cases from other postcolonial contexts underscore the shared challenges and dynamics of musical canonization. The findings reveal that Keroncong’s continued relevance lies in its adaptability. Diasporic reinterpretations, educational incorporation, and revivalist movements demonstrate that Keroncong remains a living tradition. Rather than a fixed heritage, it embodies an evolving site of identity negotiation, cultural memory, and aesthetic innovation. This study contributes to scholarly discourse on music, media, and postcolonial identity formation, offering a model for examining how musical traditions are constructed, institutionalized, and reimagined within complex socio political landscapes.